Ultrasonic Studies on the Micellar Behaviour of Non-Ionic Surfactant in Aqueous Polyelectrolyte at 303 and 313 K - Patil, T.J. (Asian Journal of Chemistry, 2010)
Ultrasonic velocities (U) and densities (ρ) have been measured for the aqueous solution of non-ionic surfactant Triton-X-100 (TX- 100) in presence of polyelectrolyte polymethacrylic acid (PMAAc) at 303 and 313 K, to understand polymer-surfactant interaction (P-S) in aqueous medium. Various acoustic parameters such as adiabatic compressibility (βad), intermolecular free length (Lf), molar sound velocity (R), specific acoustic impedance (Z), molar volume (Vm) and surface tension (γ) are evaluated using standard relations. The trends in acoustical parameters of present polymersurfactant system suggests the aggregation of surfactant micelles on to the polymer chain at critical micelle concentration (CMC) forming polymer-surfactant complex, supporting the well accepted morphology of Pearl Necklace Model.